Dry Eye Disease in Patients With Schizophrenia: A Case-Control Study - Chen, Qiankun; Wei, Zhengjiang; Wang, Leying; Xu, Xizhan; Wei, Zhenyu; Zheng, Panpan; Cao, Kai; Zhang, Zijun; Chen, Kexin; Liang, Qingfeng (Frontiers in Medicine, 2022)
Objective To evaluate the clinical features and inflammatory cytokines of dry eye disease (DED) in patients with schizophrenia. Methods This is a case-control study. The modified self-rating depression scale (M-SDS) and the ocular surface disease index (OSDI) were used to evaluate the symptoms of depression and DED, respectively. Lipid layer thickness (LLT), partial blink rate (PBR), meibomian gland loss (MGL), tear break-up time (TBUT), corneal fluorescein staining, Schirmer I-test, and eyelid margin abnormalities were also measured. A multiplex ELISA Quantibody array was used to detect the inflammatory cytokines in the tears of all participants. Results Forty schizophrenic patients and 20 control subjects were included. The mean age was 45.0 ± 9.5 years (range, 22–63 years) in schizophrenic patients and 45.4 ± 16.2 years (range, 23–76 years) in controls (P = 0.914). The ratio of male to female was 1.1 in schizophrenic patients and 1.0 in controls (P = 0.914). Ten women (52.6%) with schizophrenia and 2 (20%) in the control group (P = 0.096) were menopausal or post-menopausal. The OSDI [0.0 (0.0–4.2) vs. 7.3 (2.1–14.6)] and TBUT [4.5 (3.0–6.0) vs. 10.0 (3.5–11.0)] were significantly lower in patients with schizophrenia than in controls (P = 0.003 and P = 0.009, respectively). The rate of MGL [36.5 (17.5–47.5) vs. 8.5 (0.0–17.5)] increased in schizophrenic patients (P < 0.001). Among pro-inflammatory cytokines, the levels of interleukin (IL)-1α, IL-6, IL-11, IL-12A, IL-15, IL-17A, and granulocyte colony-stimulating factor (G-CSF) in tears were elevated in the schizophrenia group (all P < 0.01). Most of the chemokines examined were at increased levels in the tears of schizophrenics (all P < 0.05). The levels of matrix metalloproteinases-9 (MMP-9) and intercellular adhesion molecule-1 (ICAM-1) were also higher in the schizophrenic patients (all P < 0.001). The concentrations of IL-1Ra, tissue-inhibitor of metalloproteinase-1 (TIMP-1), and TIMP-2 in the schizophrenia group were decreased (all P < 0.001). In schizophrenic patients, the level of CCL2 in tears was positively correlated with OSDI (R = 0.34, P = 0.03). The increasing TIMP-1 and decreasing IL-5 were correlated with increasing LLT (R = 0.33, P = 0.035; R = −0.35, P = 0.027, respectively). The level of ICAM-1 was then positively correlated with partial blink rate (PBR) (R = 0.33, P = 0.035). There was a negative correlation between IL-8 and the Schirmer I-test (R = −0.41, P = 0.009). Conclusions Patients with schizophrenia were more likely to experience asymptomatic DED, with mild symptoms and obvious signs. The inflammatory cytokines in the tears of schizophrenic patients differed greatly from that of non-schizophrenic patients.